Transverse Colostomy Differs in Outcomes Compared to Sigmoid Colostomy: A Cohort Analysis. Issue 4 (3rd April 2022) - Dylen, Mun Yit Cheung; Lee, James Wai Kit; Ting, Lim Yi; Ragupathi, Tharun; Yu, Ng Jing; Lim, Frances; Farouk, Ridzuan; Seng, Chong Choon
Abstract: Purpose: Our aim was to identify any differences in outcomes following transverse versus sigmoid colostomy creation for management of cancer. Methods: Transverse and sigmoid colostomies are used to manage cancer-related complications including obstruction, perforation, and fistulation. The decision to use either colostomy is largely based on the surgeon's preference and the location of the cancer complication. All patients treated for cancer complications with the use of a sigmoid or transverse colostomy at National University Hospital between January 2011 and December 2016 were included. Patient characteristics and distribution frequencies were reported based on the operation performed. Post procedure morbidity and mortality was compared. Univariate and subgroup analysis were performed. Results: This was a single-center, retrospective cohort study of 93 patients who underwent a colostomy creation over a 5-year duration. Of the 93 patients included, 56 underwent a transverse colostomy (median age 59, 26 male, 30 female) and 37 a sigmoid colostomy (median age 64, 20 male, 17 female). According to univariate analysis, higher rates of stoma prolapse were seen patients with transverse colostomies. There were no differences in complications between a laparoscopic or open approach. There were no differences in the rate of other postoperative complications. Conclusion: Sigmoid colostomies were associated with a lower prolapse rate compared to transverse colostomies for cancer management. The manner of surgical approach did not affect rate of postoperative complications.